Prevalence of Occupational Health Consequences During Sugarcane Harvesting Among Harvesters of Morang District - Thapa, Bijay; Sharma, Archana (Journal of College of Medical Sciences-Nepal, 2019)
Background: Sugarcane harvesting is widely practiced in Nepal. While harvesting most of the farmers are affected regularly with small bruises, cuts, wounds, lacerations and sometimes major cut injury or even an amputation of fingers. This study aims to find the prevalence of occupational health hazards among sugarcane harvesters during the sugarcane harvesting time. Methods: The descriptive cross-sectional study was conducted at Bhaudaha VDC which is now incorporated in Katahari rural municipality, Morang. Sample size was 96 during the two weeks of study from December 2014. Convenient sampling method was used. Ethical approval was cleared from the Institutional Review Committee. Results: Most of the sugarcane harvesters were male comprising 83.3 percent. Mean age among them was 31.71. Eighty six percent of harvester had nasal congestion, 67.7% had minor cuts whereas approximately 4.2% of them had major cuts. Shoulder joint, wrist joint, neck joint and low back pains were the mostly encountered musculoskeletal pain. Conclusions: Occupational hazards among sugarcane harvesters were mostly related to the musculoskeletal problems, respiratory problems, minor cuts, major cuts and eye related problems.